Hepatosplenic abscesses in an immunocompetent child with cat-scratch disease from Peru - Alexis Alfaro del Pozo; Michelle Angulo-Cruzado; Ricardo Amenero-Vega; Alexander Álvarez-Lulichac; Hugo Fernández-Cosavalente; Joshuan Barboza-Meca; Alfonso J. Rodriguez-Morales (BMC, 2019)
Abstract Background Cat-scratch disease (CSD) is a zoonotic infection caused by Bartonella henselae and B. clarridgeiae. The typical manifestations of CSD include regional lymphadenitis and fever. However, CSD can have a wide variety of clinical manifestations that can lead to incorrect diagnoses and prolonged hospital stays. Case presentation We present a case of a 3-year-old boy admitted to the pediatric service due to prolonged fever and abdominal pain. He received empirical antimicrobial treatment due to suspicion of infection. Abdominal ultrasound showed hepatosplenic abscesses. An IFA detected the presence of IgG antibodies against B. henselae (1:256). Patient was successfully treated with azithromycin and discharged after 7 weeks. Conclusions Hepatosplenic abscesses in CSD are rarely reported, particularly in immunocompetent children, with this, only 36 cases in PubMed, Web of Sciences and Scopus bibliographical databases. High rate of suspicion and serological tests availability are of utmost importance in order to detect it and treat it successfully and promptly.